Examining the Gender and Grade Level Differences in Mathematics Anxiety - Michelle Rivera Lacia; Francisco Ben; Elizar Elizar (Proceedings of AICS - Social Sciences, 2020)
Globally, mathematics has always been perceived as a challenging subject, thus students across schooling levels have disliked mathematics leading to the feeling of anxiety towards the subject. This study investigated students’ mathematics anxiety levels across gender and grade (Grade 6 of elementary school and 4th Year of High School) in the south central part of the Philippines. The Fennema-Sherman Mathematics Anxiety Scale (FSMAS) was employed to examine the levels of mathematics anxiety of 6,672 elementary and secondary students from the seven school divisions in Region XII. The data were analysed by independent-sample t-test using SPSS 20. The results showed that there was a significant gender difference in terms of their anxiety towards mathematics. The results also indicated a significant difference on the anxiety levels between grade 6 and 4th Year of High School students, with grade 6 having the higher anxiety level compared to 4th year high school students. It is recommended to extend the study to different groups of students in different school levels using a more complex modelling and statistical methods.